A survey in Austria supports the significance of genetic counseling and pharmacogenetic testing for mental illness - Aschauer, Elena; Yazdi, Shahriar Izadi; Aschauer, Harald (Frontiers in Psychiatry, 2024)
Introduction: Genetic counseling and testing in psychiatry warrant attention, but research results on attitude, knowledge, personal experience and interest are limited. There are only a few studies that have compared the opinions of the general population and experts regarding genetic counseling and genetic testing in mental illness.This study aimed to investigate these gaps through a cross-sectional survey conducted in Austria, involving a sample of the web-active population, representative according to gender, age and geographical location (n=1,000, 24.5% of them had a psychiatric diagnosis), and experts (n=145, 83.4% of them psychiatrists). Two questionnaires were developed. Pearson chi-square statistics were used to compare responses, and regression analyses were employed to measure the strength of psycho-sociodemographic influences on answers.The findings revealed that public considered genetic counseling to be more important than experts did (68.8% versus 54.2%; Pearson chi-square 12.183; df=1; p<0.001). The general population believed that genetic testing is useful for diagnosing mental disorders, which contrasted with experts' opinions (67.9% versus 17.2%; Pearson chi-square 137.236; df=1; p<0.001). Both groups agreed on the potential benefits of pharmacogenetic testing (79% versus 80%). A small number of individuals from the public had sought genetic counseling (8%), and only a minority of experts had specific training and experience in this field (28%).Discussion: This is the first survey study on the topic conducted in Austria, with limited international studies available. Austrian experts place less value on genetic counseling compared to their counterparts in other countries. Despite recognized importance placed on genetic counseling and testing, utilization rates remain low. The value of pharmacogenetics is predicted to increase in the future. Consequently, it is crucial for medical training programs to emphasize the significance of genetic counseling and enhance the understanding of genetic aspects related to mental illnesses to enable experts to provide adequate psychoeducation and personalized care to the extent possible to patients and their families.